Droplet digital polymerase chain reaction assay for the detection of the minor clone of KIT D816V in paediatric acute myeloid leukaemia especially showing RUNX1‐RUNX1T1 transcripts. (13th June 2021) - Sasaki, Koji; Tsujimoto, Shinichi; Miyake, Mayuko; Uchiyama, Yuri; Ikeda, Junji; Yoshitomi, Masahiro; Shimosato, Yuko; Tokumasu, Mayu; Matsuo, Hidemasa; Yoshida, Kenichi; Ohki, Kentaro; Kaburagi, Taeko; et al.
Summary: KIT D816V mutation within exon 17 has been particularly reported as one of the poor prognostic factors in pediatric acute myeloid leukemia (AML) with RUNX1‐RUNX1T1 . The exact frequency and the prognostic impact of KIT D816V minor clones at diagnosis were not examined. In this study, the minor clones were examined and the prognostic significance of KIT D816V mutation in pediatric patients was investigated. Consequently, 24 KIT D816V mutations (7.2%) in 335 pediatric patients were identified, and 12 of 24 were only detected via the digital droplet polymerase chain reaction method. All 12 patients were confined in core binding factor (CBF)‐AML patients. The 5 year event‐free survival of the patients with KIT D816V mutation was significantly inferior to those without KIT D816V mutation (44.1% [95% confidence interval (CI), 16.0%–69.4%] vs. 74.7% [95% CI, 63.0%–83.2%] P ‐value = 0.02, respectively). The 5 year overall survival was not different between the two groups (92.9% [95% CI, 59.0%–NA vs. 89.7% [95% CI, 69.6%–96.8%] P ‐value = 0.607, respectively). In this study, KIT D816V minor clones in patients with CBF‐AML were confirmed and KIT D816V was considered as a risk factor for relapse in patients with RUNX1‐RUNX1T1 ‐positive AML.